Evaluation of agronomic trait of some cassava (Manihot esculenta Crantz) genotype using ground penetraiting radar - Omole, D.A. (University of Ibadan, 2023)
The main economic value of the cassava rests in its starchy storage root, but limited information is available on the growth patterns of cassava roots as compared to the shoot. A non-destructive protocol that captures root bulking rate could facilitate selection and optimize varietal response to management practices. Therefore, this study aimed to evaluate the capability of ground penetrating radar (GPR) to estimate root bulking rate six months after planting. Ten varieties were planted in Ibadan and Ikenne in the 2021/2022 cropping season using a Randomized Complete Block Design (RCBD) with 3 replications in a mixed model with variety and harvest time as a fixed factor and location as a random factor. The plot size was 30 m2, with a plant spacing of 0.8m X 1m. Data were collected on the number of roots (n), dry matter content (%), Cassava Mosaic Disease (CMD) on a scale of 1 (no visible symptom) to 5 (severe mosaic, severe leaf distortion, and stunting), plant height(cm), shoot weight (kg), root volume (lt), root girth (cm), root length (cm), total root weight (kg) and Harvest Index (HI). Fresh yield (t/ha) and dry yield (t/ha) were estimated for each variety. GPR scanning was done to obtain GPR data and was processed using "RELEASE” software, a demo version produced by IDS Georadar. Data were subjected to ANOVA using R software at α0.05. Pearson’s product-moment correlation tests were performed to compare the relationship between GPR and agronomic data sets. Multiple linear regression was used to identify traits that are significantly related to fresh root yield. Results showed a significant correlation between root volume measured by GPR and root volume measured at harvest (r=0.90***), while the number of roots measured by GPR had a significant correlation with root number measured at harvest (r=0.60***). Regression analysis indicated that root volume and dry yield had a higher coefficient of determination multiple R-squared: 0.9837. Harvest time was also significant for all traits except root volume and fresh yield. Interaction between Variety and Location was significant for CMD, root length and HI. Interaction between Variety and Harvest time was significant for all traits except plant height, root number, and dry matter. Interaction between Location and Harvest time was significant for all traits except plant height, root number and dry yield. The three-way interaction between Variety, Location and Harvest time was significant between CMD and HI. Varieties such as Arubielu, Egecoutonou, and TMEB693 had the highest plant heights range of 240cm- 260cm. Arubielu and TMS13F1160P0004 had the highest harvest index (HI) values of 0.62. VarietyTMS13F1160P0004 had the highest dry matter content of 39%. Variety IITA-TMS- IBA000070 recorded the highest fresh yield of 26 t/ha. Variety TMS13F1343P0022 had the highest dry yield of 10.10 t/ha.